Edukasi Gizi Seimbang pada Siswa di Sekolah Indonesia Kuala Lumpur: Balanced Nutrition Education for Students at Indonesian School Kuala Lumpur - Teesen, Gabriele Stefhany; Yuliani, Anita; Syabariyah, Sitti; Yualita, Perla (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
Primary school children are the beginning of providing education about balanced nutrition. Nutrition is still one of the main problems in Indonesia; schoolchildren aged 5-12 years are categorized as thin and very thin. Balanced nutrition can optimize children's growth and development; the more controlled the nutritional intake, the reduced the risk of obesity and malnutrition, so it is necessary to understand healthy and nutritious eating patterns. Sekolah Indonesia Kuala Lumpur is one of the schools for Indonesian children living in Malaysia; in SIKL, there are still Indonesian children who do not have the ideal weight, and the lack of exposure to balanced nutrition education is a factor in not ideal student bodies, according to their age. This activity aims to improve balanced nutrition education for students at an Indonesian elementary school in Kuala Lumpur. The methods used were question-and-answer discussions and filling out pre-test and post-test questionnaires. This community service activity was carried out from July to August 2023 and involved leaders of Malaysia's Aisyiyah Muhamadiyah branch organization. The activity results stated an increase in students worth 24% after being given balanced nutrition education. To maximize the provision of balanced nutrition education to students in Kuala Lumpur Indonesian schools, it is recommended to conduct further research by providing a healthy food catering program provided by the school to see changes in the quality of nutrition consumed by students.